Equity, Diversity and Inclusion moments to raise Equity, Diversity and Inclusion literacy among physician leaders - Ruzycki, Shannon M; Holroyd-Leduc, Jayna; Brown, Allison (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Implication StatementPrevious research in our department on equity-deserving groups revealed that physician leaders could improve their understanding of barriers faced by physicians from these groups. We developed EDI Moments, a brief, recurring educational intervention, to raise the EDI literacy of physician leaders in our Department of Medicine. In addition to being considered a good use of time by attendees, EDI Moments have led to new processes and policies to improve EDI in our department. Teams that implement EDI Moments should leverage local EDI expertise and select topics suited for their audience’s baseline knowledge.